The Improvement of Students Competence in Islamic Education Programme Through Tahsin Al-Quran Activities - Hakim, Rosniati (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2019)
The study is aimed at looking at students ability in reading Quran and writing the Arabic script of the holy book as well as exploring the Tahsin Al-Quran programme to improve students competence in reading and writing the script of Quran. The methods implemented in the study are both quantitative and qualitative (explanatory mixed methods design). The quantitative data was collected by testing two hundred and eight students in reading and writing the Quran script. The source of the qualitative data was ten informants consist of lecturers and students. The data is obtained through interview. The findings of the study show that (58.70%) students have good ability in reading Quran, (24.50%) students have moderate ability and (16.80%) students have poor ability in reading the holy book. Moreover, (19%) students have good ability in writing the script, (66%) students have moderate ability and the rest (15%) has poor ability in writing the script of the Quran. Related to the Tahsin Quran programme, the interview data shows that there are seven strategic steps conducted by the university to improve students competence in reading Quran. Pursuant to the finding of the study it is revealed that the students competence in reading Quran and writing the script through Tahsin activities can be improved, yet the activities requires to be more well-planned that the outcome of the learning can be better.